Tekstil işletmelerinde prim sistemi uygulamaları - Sevinç, Aytuğ (Fen Bilimleri Enstitüsü, 1997)
Bu tezde bir tekstil şirketine uygun prim sisteminin nasıl uygulanacağım incelenmiştir. Bu inceleme yapılırken sistemin uygulanmasının getireceği faydaların yanı sıra, aynı zamanda prim sisteminin bir yönetim sistemi olduğunu belirlenmiştir. Ayrıca konunun daha iyi anlaşılabilmesi için dünden bu güne gelen yönetim şekilleri ve bu yönetim şekillerinin altında yatan felsefe araştırılmıştır. Bu araştırma ve incelemelerin sonucunda prim sisteminin yönetim sistemlemleri yelpazesindeki yerini ve önemini belirlenmeye çalışılmıştır. tezin kurgusuna gelince, öncelikle yönetim biliminin tarihteki gelişimi ve niçin bu tür yönetim şekilleri ihtiyaç duyulduğu belirlenmiş; X yönetimi, Y yönetimi, Japon sistemleri toplam kalite yönetimi, Kaizen gibi kavramların anlamlan izah edilmeye çalışılmış; Yine prim sistemi uygulamalarına geçmeden önce, prim sisteminin tarihsel geçmişi incelenmiş, temel mantığı belirlenmiştir. X yönetiminden Y yönetimine geçişte prim sistemlerinin nasıl bir evrim geçirdiği ve X yönetiminden Y yönetimine geçerken (yani toplam kalite yönetimi kurarken), prim sisteminden nasıl yararlanılacağı belirlenmiştir. Prim sistemlerinin matematiksel dayanağım oluşturan zaman - etüd çalışmasının nasıl yapılacağı incelendikten sonra, ring iplik fabrikası, fantazi iplik işletmesi ve kofeksiyon fabrikası olmak üzere üç değişik tekstil fabrikasında prim sistemi uygulamaları yapılmıştır. Bu fabrikaların ortak özelliği X yönetimi uygulamalarıdır. Y yönetiminde yani toplam kalite yönetiminde ve kaizen anlayışında prim sisteminin nasıl uygulanacağı ise öneri sistemleri olarak adlandırılan ve bir kaizen uygulama sistemi olan bir örnekte incelenmeye çalışılmıştır.

The setting and application of an optimum premium system on a textile company is a complex problem. This problem is analyzed in the study. In the results of this analysis there are:. Premium system brings many benefits to the company. Premium system is a management system In the other hand the management methods from the past till today and the philosophies those they depend on are analyzed in order to achieve a brighter look to the subject. In conclusion a synthesis is made to determine the location and importance of the premium system in the range of management systems. First the history of development in the area of management is examined so that the usage and necessity of different management methods are determined; X-management, Y-management - Japan management systems and their approaches such as Total Quality Management, Kaizen etc. are examined thoroughly. Before dealing with premium system applications, the logic on which the premium system depends is designated. The deviation in premium system during the transformation from X to Y management (setting of Total Quality management) and how premium system can be used for this transformation are determined. The procedure of time-measurement on which the mathematical theory of premium systems depends is planned, then the premium system is applied to three different textile factories which are:. Ring Yarn factory.. Fancy yarn factory. Clothing factory The common characteristic of these factories is the X management they use. The application of premium system to Y management in other words total quality management and Kaizen approach is discussed on an example which is a Kaizen application and called suggestion systems. The most important difference between the premium system under X management and the öne under Y management is the criterion according to which the premium amounts are calculated. in X management system the premium is given for production that is the muscle power of the worker. Furthermore in Y system the premium is given for a useful idea which develops the process (improving the quality and productivity ete.) that is the brain power of the worker. The worker gets the premium if he works harder in X management but if he generates ideas those make the process easier and eliminate the errors in Y management. The criterion of premium is very important. The criterion of premium must be parallel to the needs and the goals of the company. There are many examples of successful premium systems because of their true target. Therefore a company can design its premium system solution which is targeted toward öne of productivity, quality ör development ör ali together accordhıg to the policy of the company and its planned place in market. Generally X ör similar management systems are used in Turkish Textile Industry so that the premium system applications take place *. * vııı usually under X management and oriented in production mostly, also some punishment methods are used to improve quality. An other noticeable subject is there is no premium data, such as premium scales, included in the result report of any premium application sample analyzed. Because the unit of calculations and numerical values are not so important, the important thing is the way followed for success in the premium system application. it is obvious that the numerical data will loose its meaning in few years time. The success is the result, than to know how the success is achieved and to learn the premium system is the principle. Especially in production oriented premium systems, generally in ali premium systems the premium is given relative to a measurable criterion so that the necessity of setting the justest system as much as possible is at least important as the quantity of the premium. Naturally it must never be forgotten that the measurable criterion of the premium system should be directly proportional to the process of the worker. Othenvise the Premium will have no meaning more than a increase in the salary of the worker. For an example premium should be given to a quality control worker not for the number of product he controlled per unit time, but for the minority of the discarded products he approved by mistake. Finally, what a good premium system need, will be examined Premium systems always contain the logic of "who works harder, gets more money". in these systems managers must keep their promises. A premium system should be fair and practice. But more important thing is the enough premium which is given to workers. If the workers can not get their labor of this work of his work, that premium system can not continue ix Targets and borders must be determined by statistical works. A person who increases his work tempo to %100 ör up must get a good premium. A worker who works with a tempo %100 should get 1A of his salary as premium. If the number of persons who get the most premium %5 these premiums should be %70-50 of their salaries. If these elements can be applied, the premium system will be successful and performance - production - quality quickly increase. How can we determine a premium system works ör not ? What should be done in this situation ? 1) Production does not increase. 2) in the beginning, production and quality increase but after both of them decrease. 3) Production increase but quality decrease. The question below must be answered to understand how bad works the premium system. And so we can determine which the alternative damaged system is in Are the people educated and motivated about the premium system. How much is the average of the proportion of premium to salary that the workers and the worker group which %5 of the highest premium group get. What are the general complains of the workers? Did a system which checks the quality set up ? After these questions were asked probably we will meet these answers x First case: The premium system could not be explained to the workers and a trustiness is existing The premium quantity is so low according to salary and a little group succeed to get premium The workers are complainer Second case: Everybody know premium system and believe of its benefit. in the beginning everybody göt premium but after the average of the proportion of premium to salary decreased. in the time a decrease to the fîrst situation was seen. The worker's complaints increased Complaints a) premium system is unfair and can not separate who works most and who works not b) The amount of premium is low. The workers can not get real premium although Üıey work hard. Generally complaints are about these subjects and workers do not trust to the premium system. Third case: Ali of worker's percentage of premium to salary increase, Workers are pleased. But there is not any control consequently quality is decreasing and boss is not pleased Ali of the three cases, premium system did not give the desire. Now, what can we do to activate the premium system in order to our desire ? xi For the first case, motivation should be increased by meeting and the design of premium system should be described For the second case, injustices of the premium system should be terminated and the amount of premiums should be increased. The improvement of the premium system should be described in order to increase the trust of the workers. For the third case, a useful quality control mechanism should be set up. Also premium can be given for quality. These should be done for both of other cases...
Applications for increasing productivity by dealing with the worker in textile industry
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 1997
Keywords: Prim sistemi; Tekstil endüstrisi; Yönetim sistemleri; Premium system; Textile industry; Management systems